A 35-year-old male with Waldenstrom Macroglobulinemia - Tamina Hossain; Dewan, Afrin; Rahman, Atikur; Das, Nihar Ranjan; Uddin, M M Nasir; Hoque Chowdhury, Mir Mahfuzul; Islam, Mohammad Rafiqul (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Waldenstrom macroglobulinemia is one type of non- Hodgkin lymphoma that presents with a wide range of clinical features mainly due to secretion of the IgM paraprotein and infiltration of lymphoplasmacytic cells. Patients with Waldenstrom macroglobulinemia may experience fatigue, unexplained weight loss, enlarged lymph nodes, abdominal swelling, weakness, nose bleeding, blurring of vision etc. Waldenstrom macroglobulinemia is a disease of elderly individuals. The median age at diagnosis is 65 years, with a slight male predominance. We reported a case of a 35-yearold male who presented with fever, abdominal pain, loose motion and epistaxis. Examination revealed cervical and inguinal lymphadenopathy with hepatosplenomegaly. Investigation revealed diffuse lymphocyte infiltration on bone marrow study . Protein electrophoresis showed monoclonal gammopathy with high serum IgM level. On the basis of clinical features and investigation reports finally we diagnosed that, this was a rare case of Waldenstrom macroglobulinemia in a young patient. The patient was transfused 5 units of whole blood and was treated following standard treatment protocol with dexamethasone, Bortezomib and G-CSF. Unfortunately, patient died 3 weeks after initiation of treatment. J Bangladesh Coll Phys Surg 2023; 41(4): 325-328